Effect Phenytoin Therapy to Fibroblasts and Angiogenesis of Enterocutaneous Fistula in Wistar Rat - Muhammad Budiman Irpan Bachtiar; Hermawan; Hardian; Ignatius Riwanto (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Comprehensive wound care in enterocutaneous fistula (ECF) is the therapeutic of choicecurrently, which may increase of closure rate without surgery from 19 to 92%. Phenytoin has been reportedhave anticolagenase effect on wound healing is hoped to improve the ECF closure.Aim: The study was aimed to demonstrate the effect of phenytoin on closure of enterocutaneous fistula seenfrom the number of fibroblasts and angiogenesisMethods: This study was “Randomized Controlled trial with post test only group design” on 18 malewistar rats with ECF, that were divided randomly into three groups: group(K) control, P1(topical phenytoin),P2(oral phenytoin). After 7 days of treatment, they were terminated and histopathological examinations wereperformed to do fibroblast cell counting and the amount of angiogenesis by Hematoxilin Eosin staining.Results: Mean of the number of fibroblastin groups K, P1 and P2 were 69.50 ± 10.07, 155.50 ± 13.50 and182.16 ± 11.85 respectively (One way Anova P=0.001) and mean of the number of angiogenesis in groupsK, P1, and P2 were 95.66 ± 9.72, 178.66 ± 11.75, and 205,16 ± 9.74 respectively (One way Anova P=0.001).Post Hoc Test LSD showed thatthe number of fibroblast of group P1 vs K(P=0.001), P2 vs K(P=0.001),P1 vs P2(P=0.004) and the number of angiogenesis of group P1 vs K(P=0.001), P2 vs K(P=0.001), P2 vsP1(P=0.002).Conclusion: The therapy of topical and oral phenytoin increased the number of fibroblasts and angiogenesisin Wistar rat with ECF. Out come of oral phenytoin therapy better than topical.